2013
DOI: 10.1016/j.febslet.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin regulates hippocampal 14‐3‐3ζ protein levels

Abstract: Transthyretin is the carrier protein of thyroxine and retinol in plasma and cerebrospinal fluid and has been described also as a neuroprotective molecule. 14-3-3 Proteins are very important in many cellular processes, being their absence related with deficits in memory and learning. The analysis of the relationship between these two proteins is the main objective of this work. We found that hippocampi of young TTR null mice presented lower levels of 14-3-3ζ protein, but no changes in gene expression when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Hippocampus of young TTR null mice presented lower levels of 14-3-3ζ protein, but no changes in gene expression. Lysosomal degradation of 14-3-3ζ in the absence of TTR was the mechanism proposed for the reduced 14-3-3ζ levels (89). Hippocampal slice cultures of TTR null mice did not present increased cellular death when compared wild-type animals (90), suggesting that the decreased levels of 14-3-3ζ observed in these animals are not associated with increased cellular death.…”
Section: Ttr In the Nervous Systemmentioning
confidence: 88%
“…Hippocampus of young TTR null mice presented lower levels of 14-3-3ζ protein, but no changes in gene expression. Lysosomal degradation of 14-3-3ζ in the absence of TTR was the mechanism proposed for the reduced 14-3-3ζ levels (89). Hippocampal slice cultures of TTR null mice did not present increased cellular death when compared wild-type animals (90), suggesting that the decreased levels of 14-3-3ζ observed in these animals are not associated with increased cellular death.…”
Section: Ttr In the Nervous Systemmentioning
confidence: 88%
“…In addition, during the last years, several other functions have been associated with this molecule, like its potential role in high-density lipoprotein biology [5], cognition [6], neuroprotection after cerebral ischemia [7] via a megalin dependent pathway [8], modulation of Aβ aggregation [9], regulation of 14-3-3ζ metabolism [10], or glucose homeostasis [11]. However, the existence of genetic point mutations may alter the quaternary structural stability of TTR [12], leading to its dissociation into non-native species which self-assemble and polymerize, ultimately depositing in the extracellular matrix and disrupting normal tissue function [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been described that tyrosine 3‐monooxygenase/tryptophan 5‐monooxygenase activation protein, zeta (14‐3‐3zeta or YWHAZ) expression levels decreased with aging . Also, Vieira et al, 2013 showed that TTR regulates YWHAZ protein levels and so the absence of TTR correlated with decreased levels of YWHAZ in the hippocampus in young/adult TTR null mice when compared to TTR wild‐type animals, although no changes in gene expression were found …”
Section: Introductionmentioning
confidence: 99%